Rh Alloantibodies in Rh D Negative Blood Group Pregnant Women - A Regional Transfusion Centre Study - Bajwa, Hussan; Alam, Maqbool; Rathore, Muhammad Ali; Yazdani, Muhammad Sajid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of Rh alloantibodies in pregnant women of the Rh-D negative blood group. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Transfusion (AFIT) Rawalpindi, from Jan to Dec 2017. Methodology: The blood samples of pregnant women received for blood grouping, cross matching and antibodies screening were included in the study. The blood was typed for Rh-D along with ABO blood groups by Column Agglutination Technique (CAT), commonly known as the gel card method. Then, the samples included in the study were subjected to antibody screening by three cell antibody screening panel (Dia Cell, a product of Bio-Rad) by Column Agglutination Technique. The samples with positive antibody screening were further processed by 11 cell antibody screening panel (Dia Cell, BioRad) for Rh antibody identification by Column Agglutination Technique, the same as the indirect antiglobulin test (IAT). Results: 453 Rh-D negative pregnant women were screened for alloantibodies during the study period. Rh alloantibodies were present in 55 (12.08%) cases. The most common alloantibody identified was anti-D in 48 (87.3%) samples, followed by anti-C in 6 (10.9%) and anti-E in 1 (1.8%) case. Conclusion: The most prevalent Rh alloantibody identified in Rh-D negative pregnant women was anti-D, while the anti-C and anti-E were less prevalent. However, no case of anti-c and anti-e alloantibody was identified.